Kenaf Reinforced PLA Composite Thermoforming: A Numerical Simulation - Mohd Radzuan, Nabilah Afiqah; Sulong, Abu Bakar; Mamat, Mohd Rizal; Tharazi, Izdihar; Tholibon, Dulina; Dweiri, Radwan; Hammadi, Mohannad Saleh (International Journal of Integrated Engineering, 2018)
Recent manufacturing development focuses on the optimum technique of product fabrication that time-consuming and cost-effective including thermoforming process. Fundamental studies on the thermoforming process, especially in the uni-directional direction of kenaf fiber composite are still in preliminary stages. Hence, a numerical simulation is performed in order to minimize the experimental conduct. PAM-FORM software is used for modeling and simulation of the thermoforming process by studying the effect of processing parameters on the results of the simulation. The optimum thermoforming process parameter in terms of temperature, puncher speed, puncher radius and composite thickness are determined by the design of experiments. The output parameters including thinning of the composite, shear angle and stress are analyzed to identify the wrinkling defects which further analyzed using the Design-Expert software. Results demonstrate that at a temperature of 120 Â°C, puncher speed of 28.78 m/s, puncher radius and composite thickness of 4 mm and 2 mm, respectively able to achieve minimum thinning and minimal shear angle during the thermoforming process.